Tracing social history from synchronic linguistic and ethnographic data: The prehistory of Resígaro contact with Bora (2015)
The Amazonian language Resígaro was heavily influenced by the unrelated, neighboring Bora language. Bora influence involves cultural assimilation, some loanwords, and heavy morphological borrowing. What social circumstances lead to this influence? This paper reviews our current knowledge about the cultural and linguistic features that Resígaro borrowed from Bora and interprets these as reflecting a particular social history involving bilingualism and ceremonial exchange.